Sulfur dioxide leaching of zinc sulfide - McGinnity, Justin (Curtin University, 2001)
Studies were conducted into the mechanism and kinetics of the dissolution of synthetic zinc sulfide and zinc concentrate in aqueous solutions containing sulfur dioxide.Experiments at ambient temperature established that the dissolution of ZnS in aqueous solutions of sulfur dioxide proceeds via acidic non-oxidative dissolution and not by direct reaction of the sulfide with S02(aq). The non-oxidative dissolution reaction generates H2S(aq) or HS-(aq) species which are thought to rapidly react with sulfurous acid species, S02(aq) or HS03-(aq), to possibly produce initially sulfane monosulfonates as intermediates, followed by sulfane disulfonates and elemental sulfur. The formation of sulfane monosulfonates is postulated based upon inhibition observed in ZnS / S02 leaches which is not attributable to either H2S(aq) or occlusion elemental sulfur.At elevated temperatures (100oC - 200oC) the rate of ZnS dissolution in sulfurous acid is affected by the thermal decomposition of sulfurous acid, which produces sulfuric acid, which leaches the mineral non-oxidatively. Increasing the temperature increases the rate of thermal decomposition of sulfurous acid and consequently, the rate of sulfuric acid formation, increasing the rate of ZnS dissolution.The kinetics of the dissolution of ZnS in solutions of sulfuric acid and sulfur dioxide were investigated at temperatures up to 200oC. At 100oC and 150oC, the dissolution of ZnS in H2SO4 was found to obey the relationd[Zn2+]/dt = kfAs[H+] krAs[H2S(aq)]1/2[Zn2+]1/2and equilibria and rate constants for the ZnS / H2S04 reaction were obtained over the range, 100oC to 200oC. The activation energies of the forward and reverse reactions were found to be 56 +/- 11 kJ mol-1 and 45 +/- 15 kJ mol-1, respectively. The equilibrium constants were 4.99x10-4, 1.26x10-3 and 2.83x10-3 at 100oC, 150oC and 200oC, respectively.In the presence of added S02, at low ZnS pulp density (0.5 g L-1), the rate of ZnS dissolution in sulfuric acid increased due to the removal of H2S(aq) by reaction with S02(aq) or HS03-(aq). However the increase in rate was much less than that expected for the complete removal of H2S(aq). As with leaches of ZnS in sulfurous acid at ambient temperature, the inhibition was not attributable to the presence of residual H2S(aq) or to occlusion of unreacted ZnS by elemental sulfur, but is thought to be due to aqueous species that are like "H2S", in that they may react with Zn2+ to reprecipitate W.To this end, sulfane monosulfonates have again been postulated. The rate of ZnS dissolution, under conditions of low pulp density, was independent Of S02 concentration, suggesting that under these conditions the rate of the H2S / S02 reaction is also independent of the S02 concentration.At higher pulp densities (200 g L-1), similar to those expected in an industrial application, synthetic zinc sulfide leached rapidly in H2S04 / S02 solutions to approximately 60% zinc extraction, but was then inhibited by the large amounts of sulfur that formed. These caused agglomerates of zinc sulfide and elemental sulfur to form, even at temperatures below the melting point of sulfur, reducing the surface area of zinc sulfide available for reaction.Leaches of zinc concentrate at low pulp densities in H2S04 / S02 solutions and at temperatures above sulfur's meting point, were inhibited by the formation of molten sulfur. In contrast to synthetic zinc sulfide, zinc concentrate is readily wet by molten sulfur. Three surfactants orthophenylenediamine, quebracho and sodium ligninsulfonate were found to be reasonably effective in preventing molten sulfur from occluding the mineral surface. At high pulp densities, the H2S04 / S02 leach solution was unable to effect, the extraction of zinc from a zinc concentrate beyond approximately 10%.Integral S02 / H2S04 leaching of zinc concentrate was found not to be a commercial prospect. However, sidestream processing of zinc concentrate in an acid leach stage followed by reaction of generated H2S with S02 from the roasting stage to produce elemental sulfur may be viable.